STUDI EKSPERIMEN KUAT TEKAN BETONMENGGUNAKAN SEMEN PPC DENGAN TAMBAHAN GLENIUM - Yolanda, F Windy; Mungok, Chrisna Djaya; Samsurizal, Eddy (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
This paperpresents the results ofthe use ofmaterialadded glenium mixed into thenormal concrete mixing with varying levels of 0,5 litre, 0,7 litre, and 1 litre. Specimens made cylindrical size Ã˜ 15 cmand height 30 cm.alms to determine the ratio of Increse in concrete compressive strength normal to the additional Glenium which varies using PPC cement.Â  This paper using Job mix formula ACI modification. The characteristics of the compressive strength of concrete age 28 days using Glenium (o,5 litre, 0,7 litre, and 1 litre) successive reach (29,66 MPa; 42,92 MPa; 27 MPa; 30,26 MPa). The result of pull apart strength test (3,55 MPa; 4,68 MPa; 4,03 MPa;4,04 MPa). And the result of modulus elasticity test (12539.21MPa;13928.36 MPa; 17481.47 MPa; 12583.67 MPa).